Consistency in adult reporting of adverse childhood experiences. Issue 3 (29th October 2015) - Colman, I.; Kingsbury, M.; Garad, Y.; Zeng, Y.; Naicker, K.; Patten, S.; Jones, P. B.; Wild, T. C.; Thompson, A. H.
Abstract : Background: Many studies have used retrospective reports to assess the long-term consequences of early life stress. However, current individual characteristics and experiences may bias the recall of these reports. In particular, depressed mood may increase the likelihood of recall of negative experiences. The aim of the study was to assess whether specific factors are associated with consistency in the reporting of childhood adverse experiences. Method: The sample comprised 7466 adults from Canada's National Population Health Survey who had reported on seven childhood adverse experiences in 1994/1995 and 2006/2007. Logistic regression was used to explore differences between those who consistently reported adverse experiences and those whose reports were inconsistent. Results: Among those retrospectively reporting on childhood traumatic experiences in 1994/1995 and 2006/2007, 39% were inconsistent in their reports of these experiences. The development of depression, increasing levels of psychological distress, as well as increasing work and chronic stress were associated with an increasing likelihood of reporting a childhood adverse experience in 2006/2007 that had not been previously reported. Increases in mastery were associated with reduced likelihood of new reporting of a childhood adverse experience in 2006/2007. The development of depression and increases in chronic stress and psychological distress were also associated with reduced likelihood of 'forgetting' a previously reported event. Conclusions: Concurrent mental health factors may influence the reporting of traumatic childhood experiences. Studies that use retrospective reporting to estimate associations between childhood adversity and adult outcomes associated with mental health may be biased.